Acute pancreatitis-associated pancreatic panniculitis - Elguera-Falcón, Federico (2019)
A 52-year-old male with a past history of acute pancreatitis four years before, and now he entered with a 30-day disease duration with painful violaceous tumors on the lower limbs. The skin biopsy study was compatible with pancreatic panniculitis. During hospitalization the patient had a new episode of mild pancreatitis with positive response to the standard treatment, with resolution of the skin lesions.